The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1093/applin/amaa030
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Usage-based Principles in the Development of L2 Finnish Evaluative Constructions

Abstract: This study investigates the formal verbalizations of evaluation used by four beginning L2 learners of Finnish from a dynamic usage-based perspective. Longitudinal data collected weekly were used to investigate what kind of constructions learners use to express evaluation and how these interact and develop over time. The results show that when a new construction is acquired in the L2, another related construction might regress. The results also point to increased variability in the construction during a phase o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…The varied and flexible associations between the development of linguistic subsystems are indicative of the interconnectedness as a characteristics of complex and dynamic systems. An interesting observation which was reported several times is that more variability and fluctuation in second language development seems to correlate with increased proficiency (Gui et al, 2021;Huang et al, 2021;Lesonen, 2021). The study conducted by Zhang et al (2022) showed that among the three prototypes of learners, the prototype with constant variability in the development had more overall progress compared to the other prototypes.…”
Section: Discussionmentioning
confidence: 93%
“…The varied and flexible associations between the development of linguistic subsystems are indicative of the interconnectedness as a characteristics of complex and dynamic systems. An interesting observation which was reported several times is that more variability and fluctuation in second language development seems to correlate with increased proficiency (Gui et al, 2021;Huang et al, 2021;Lesonen, 2021). The study conducted by Zhang et al (2022) showed that among the three prototypes of learners, the prototype with constant variability in the development had more overall progress compared to the other prototypes.…”
Section: Discussionmentioning
confidence: 93%
“…Language is used in social interaction to achieve certain communicative goals that vary from general intentions such as requesting help or sharing emotions to more specific goals (Schmid, 2020), such as getting across the idea that there are many lakes in Finland. Proficient speakers may choose among different kinds of conventionalized linguistic solutions in the speech community to achieve a certain communicative goal (e.g., Fernández-Domínguez, 2019;Lesonen et al, 2021;Schmid, 2020). Conventionalized links between communicative goals and linguistic forms are usually referred to as constructions (e.g., Goldberg, 2006).…”
Section: Investigating L2 Learners' Linguistic Means: the Onomasiolog...mentioning
confidence: 99%
“…One finding that is consistently emerging from the growing body of usage-based research is that the exemplar-based trajectory is not necessarily a path from "one to many" but can also be from "a few to more" in a process where constructions that are partially specific and partially schematic (for example, "Are you + ADJECTIVE?" in L2 English question formation) play an essential role across phases in development (Eskildsen, 2015, Eskildsen 2017, Eskildsen 2020aLesonen et al, 2018, Lesonen et al, 2020a, Lesonen et al, 2020bHorbowicz and Nordanger, 2022). However, recent research is showing that a usage-based trajectory may also be a matter of routinisation (Eskildsen, 2020a;Pekarek Doehler and Balaman, 2021).…”
Section: Longitudinal Conversation Analysis-based and Usage-based Studies In L2 Researchmentioning
confidence: 99%